STUDY OF HEAT EFFECTS IN TOPOCHEMICAL PROCESSES OF CELLULOSE ESTERIFICATION - Michael Yacob Ioelovich (Химия растительного сырья, 2024)
In this research, the heat effects of topochemical esterification of cellulose, namely, nitration and acetylation, were studied. Depending on the conditions, the esterification process can occur in two main topochemical directions such as bulk and local. In bulk process the reagent quickly penetrates in amorphous domains (ADs), and more slowly in crystallites (CRs) of cellulose. In local esterification, the reagent penetrates the most accessible ADs only, whereas CRs remain almost unreacted. It was found that the reaction of bulk nitration of cellulose up to a substitution degree (DS) of 1.5 is endothermic and determined primarily by the contribution of the temperature-entropy component to the negative Gibbs potential. However, if DS > 1.5, the bulk nitration becomes exothermic, and therefore, the feasibility of this process is determined by the impact of enthalpy on the negative Gibbs potential. Unlike nitration, the bulk acetylation of cellulose is always an exothermic process, regardless of the achieved degree of substitution, and this process can be implemented due to the predominant contribution of reaction enthalpy to negative Gibbs potential. In the case of local esterification of ADs, the main contribution to the negative Gibbs potential is made by the reaction enthalpy that determines the reaction feasibility. Besides, the local acetylation is more exothermic than the local nitration process.